Strengthening Student Competency in Making Social Science Learning Media, Social Science Development Courses - Tutuk Ningsih; Gautam Kumar Jha (Yayasan Keluarga Guru Mandiri, 2021)
The teaching and learning process is not only limited to providing material, but also utilizing media that is suitable with the material to be taught. Learning media has a very important role, therefore the media in learning has a function as a tool in the teaching and learning process to engage students to be active in learning. Social science learning process requires learning media to be used by teachers to stimulate students' minds. This study aims to describe and analyze the strengthening of student competencies in making social studies learning media in Social Development courses in the Postgraduate Study Program at IAIN Purwokerto. This type of research is a qualitative study. Data collection techniques used are through observation, interviews and documentation. Development of student competency in Madrasah Ibtidaiyah Teacher Education Study Program IAIN Purwokerto develops learning media especially social science subjects at the Madrasah Ibtidaiyah education level. The results of competency development is learning media that can be used by teachers in delivering material in social science subjects. The development of media produced by students is in the form of Mini Zoo media, ASEAN Box media and Traditional and Modern Markets Miniature media.